Material Transfer Behavior between a Blade and Two Types of Coating during High-Speed Rubbing. Issue 5 (3rd September 2018) - Xue, Weihai; Gao, Siyang; Duan, Deli; Zhang, Jiaping; Liu, Yang; Li, Shu
ABSTRACT: The material transfer behaviors of Al-hBN and NiAl-hBN coatings rubbed by a Ti6Al4 V blade at different linear speeds and single pass depths were studied using a high-speed rubbing tester. The blade height variation analysis, morphologies, energy-dispersive spectroscopy, and X-ray diffraction studies of the blade and the coating wear scars indicated that the coating material transferred to the blade during rubbing with the Al-hBN coating. For the NiAl-hBN coating, the blade material transferred to the coating. The temperature differences at the interface, varying melting points of the coatings, and blade plastic flow softening under high temperatures were regarded as factors for different material transfer behaviors.